From spirituality to innovation: How spiritual leadership drives mosque management innovation - Thoha, Ahmad Faiz Khudlari; Hidayat, Hidayat; Mauludi, Mauludi (Jurnal Inovasi Ekonomi, 2024)
In recent years, there has been increased acknowledgment of spirituality in the workplace and its potential influence on organizational outcomes, including creative work behavior. This study examines the impact of spiritual leadership on driving innovative work behavior within mosque management teams in Surabaya, with a specific focus on the mediating role of spiritual well-being. Survey data from 106 team members were analyzed using Structural Equation Modeling (SEM), revealing that spiritual leadership positively influences creative work behavior, with spiritual well-being partially mediating this relationship. This research contributes to the existing literature on the intersection of spirituality and innovation by investigating how spiritual leadership fosters an innovative culture within mosque administration. Furthermore, it extends the application of spiritual leadership theory to religious non-profit organizations, an area that has remained unexplored. The findings have practical implications for mosque leaders and managers seeking to promote innovation within their organizations by emphasizing spiritual leadership and well-being to enhance their teams' innovation capabilities.